Lincoln and Freedom : Slavery, Emancipation, and the Thirteenth Amendment - Gabbard, Sara Vaughn; Holzer, Harold (Book collections on Project MUSE., 2007)
Lincoln's reelection in 1864 was a pivotal moment in the history of the United States. The Emancipation Proclamation had officially gone into effect on January 1, 1863, and the proposed Thirteenth Amendment had become a campaign issue. Lincoln and Freedom: Slavery, Emancipation, and the Thirteenth Amendment captures these historic times, profiling the individuals, events, and enactments that led to slavery's abolition. Fifteen leading Lincoln scholars contribute to this collection, covering slavery from its roots in 1619 Jamestown, through the adoption of the Co.